Academy and architecture its development processes and its relationship with society (2022)
This reflection article exposes how, among the variety of factors that guide the transformation process suffered by the contemporary city, the academy is occupying a forceful and definitive space. The rupture that has been created in the teacher-student relationship is taken as a point of analysis, because that is the central axis of education, and even more so when it comes to the teaching of disciplines such as architecture, since in these the ability to transmit the knowledge acquired correctly and precisely is fundamental, in order to continue the tangible and intangible cultural heritage that our ancestors have left us.